2018
DOI: 10.31234/osf.io/eaz3d
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Heritability of Self-Control: a Meta-Analysis

Abstract: Self-control is the ability to control one’s impulses when faced with challenges or temptations, and is robustly associated with physiological and psychological well-being. Twin studies show that self-control is heritable, but estimates range between 0% and 90%, making it difficult to draw firm conclusions. The aim of this study was to perform a meta-analysis to provide a quantitative overview of the heritability of self-control. A systematic search resulted in 31 included studies, based on a sample size of &a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 63 publications
2
34
0
Order By: Relevance
“…In addition, since self-control is a crucial asset, enhancing individuals’ self-control ability might help buffer the influence of negative appraisal and improve the public’s mental health. We need to point out that although self-control has its heritable underpinnings, self-control can still be shaped by the environment [ 27 ] and develops within individuals throughout the life span [ 28 ]. Prior research found some programs to be useful in improving individuals’ self-control effectively, such as mediation [ 29 ] and comprehensive self-control training [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since self-control is a crucial asset, enhancing individuals’ self-control ability might help buffer the influence of negative appraisal and improve the public’s mental health. We need to point out that although self-control has its heritable underpinnings, self-control can still be shaped by the environment [ 27 ] and develops within individuals throughout the life span [ 28 ]. Prior research found some programs to be useful in improving individuals’ self-control effectively, such as mediation [ 29 ] and comprehensive self-control training [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The shared genetic makeup of children and parents might also be correlated with the social environment they encounter, through gene-environment correlation (rGE). For instance, parents may transmit a genetic liability for antisocial behavior to the child and simultaneously provide an abusive rearing environment ( Jaffee et al, 2004 ), or may transmit a genetic disposition for high behavioral control and create a tidy and organized home environment ( Willems et al, 2019 ). This association between the genotype a child inherits from his or her parents and the environment in which the child is raised is referred to as passive gene–environment correlation (passive rGE).…”
Section: Disentangling Genetic and Non-genetic Transmissionmentioning
confidence: 99%
“…Aspirations are a significant factor that should be taken into account when supporting adolescents with low self-control, at risk for mental health problems, and/ or involved with criminal activities (Fergusson et al, 2013;Moffitt et al, 2011). Previous longitudinal twin studies have revealed that low self-control is relatively stable during the life course, and could be robustly explained by genetic factors (Beaver et al, 2009(Beaver et al, , 2008Willems et al, 2019). It is not easy to enhance self-control among adolescents with low intrinsic aspirations; however, enhancing intrinsic aspirations could effectively promote later life satisfaction.…”
Section: Discussionmentioning
confidence: 99%